A Juridical Analysis of the Validity of General Meeting of Shareholders’ Resolutions in Cases of Procedural and Organizational Deviations - Kuistono, Caesar Andre; Adam, Richard C. (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The General Meeting of Shareholders (GMS), as the highest governing body of a Limited Liability Company, must be conducted in accordance with the formal and material procedures mandated by Law Number 40 of 2007 to ensure that its resolutions carry binding legal effect. This study employs a normative legal research method using a statutory approach to examine the validity of GMS resolutions in instances of procedural deviation, including improper notice, omission of the meeting agenda, or failure to satisfy attendance and decision-making quorum requirements. The findings show that such procedural violations generally render GMS resolutions invalid and may provide grounds for shareholders to file a claim before the district court under Article 61 of the Company Law, except in situations where all shareholders are present and unanimously approve the resolutions as permitted under Article 82(5). Beyond invalidating resolutions, procedural deviations may also give rise to civil liability for directors or commissioners, underscoring the importance of adherence to GMS procedures in safeguarding shareholder rights and supporting sound corporate governance